A critical appraisal of paliperidone long-acting injection in the treatment of schizoaffective disorder - Chue P; Chue J (Dove Medical Press, 2016)
Pierre Chue,1 James Chue2 1Department of Psychiatry, University of Alberta, 2Clinical Trials and Research Program, Edmonton, AB, Canada Abstract: Schizoaffective disorder (SCA) is a chronic and disabling mental illness that presents with mixed symptoms of schizophrenia and affective disorders. SCA is recognized as a discrete disorder, but with greater heterogeneity and symptom overlap, leading to difficulty and delay in diagnosis. Although the overall prognosis is intermediate between schizophrenia and mood disorders, SCA is associated with higher rates of suicide and hospitalization than schizophrenia. No treatment guidelines exist for SCA, and treatment is frequently complex, involving off-label use and polypharmacy (typically combinations of antipsychotics, mood stabilizers, and antidepressants). Oral paliperidone extended-release was the first agent to be approved for the treatment of SCA. As in schizophrenia and bipolar disorder, adherence to oral medications is poor, further contributing to suboptimal outcomes. The use of an antipsychotic in a long-acting injection (LAI) addresses adherence issues, thus potentially reducing relapse. Paliperidone palmitate represents the LAI formulation of paliperidone. In a long-term, double-blind, randomized, controlled trial of adult patients (n=334; intent-to-treat [ITT]) with SCA, paliperidone long-acting injection (PLAI) significantly delayed risk of relapse compared to placebo (hazard ratio 2.49, 95% confidence interval, 1.55–3.99; P<0.001). This study demonstrated the efficacy and safety of PLAI when used as either monotherapy or adjunctive therapy for the maintenance treatment of SCA. The results are consistent with a similarly designed study conducted in patients with schizophrenia, which suggests a benefit in the long-term control of not only psychotic but also affective symptoms. No new safety signals were observed. When used in monotherapy, PLAI simplifies treatment by reducing complex pharmacotherapy and obviating the necessity for daily oral medications. PLAI is the second agent, and the first LAI, to be approved for the treatment of SCA; as an LAI formulation, there is the advantage of improved adherence and simplified treatment in the long-term management of SCA. Keywords: second-generation antipsychotics, paliperidone palmitate, long-acting injection, schizoaffective disorder